High tech and high touch : headhunting, technology, and economic transformation - Coverdill, James E.; Finlay, William, 1955- (ILR Press, an imprint of Cornell University Press, 2017)
In High Tech and High Touch, James E. Coverdill and William Finlay invite readers into the dynamic world of headhunters, personnel professionals who acquire talent for businesses and other organizations on a contingent-fee basis. In a high-tech world where social media platforms have simplified direct contact between employers and job seekers, Coverdill and Finlay acknowledge, it is relatively easy to find large numbers of apparently qualified candidates. However, the authors demonstrate that headhunters serve a valuable purpose in bringing high-touch search into the labor market: they help parties on both sides of the transaction to define their needs and articulate what they have to offer. As well as providing valuable information for sociologists and economists, High Tech and High Touch demonstrates how headhunters approach practical issues such as identifying and attracting candidates; how they solicit, secure, and evaluate search assignments from client companies; and how they strive to broker interactions between candidates and clients to maximize the likelihood that the right people land in the right jobs.